Antimicrobial Susceptibility, Virulence, and Genomic Features of a Hypervirulent Serotype K2, ST65 Klebsiella pneumoniae Causing Meningitis in Italy - Aurora Piazza; Matteo Perini; Carola Mauri; Francesco Comandatore; Elisa Meroni; Francesco Luzzaro; Luigi Principe (MDPI AG, 2022)
The rise of a new hypervirulent variant of Klebsiella pneumoniae (hvKp) was recently reported, mainly linked to the ST23 lineage. The hvKp variants can cause severe infections, including hepatic abscesses, bacteremia, and meningitis, with a particularly disconcerting propensity to cause community-acquired, life-threatening infection among young and otherwise healthy individuals. The present study aimed to report the clinical characteristics of a hypermucoviscous K. pneumoniae strain isolated in Italy and sustaining recurrent meningitis in a patient of Peruvian origin. A further objective was to retrospectively investigate, by means of whole-genome sequencing (WGS) analysis, the genomic features of such an isolate. The hypermucoviscosity phenotype of the strain (sk205y205t) was determined using the string test. Genomic information was obtained by WGS (Illumina) and bioinformatic analysis. Strain sk205y205t was susceptible to most antibiotics, despite the presence of some resistance genes, including blaSHV-11, blaSHV-67, fosA, and acrR. The isolate belonged to ST65 and serotype K2, and exhibited several virulence factors related to the hvKp variant. Among these, were the siderophore genes entB, irp2, iroN, iroB, and iucA; the capsule-regulating genes rmpA and rmpA2; and the type 1 and 3 fimbriae fimH27 and mrkD, respectively. A further operon, encoding the genotoxin colibactin (clbA-Q), was also identified. The virulence plasmids pK2044, pRJA166b, and pNDM. MAR were also detected. Phylogenetic investigation showed that this Italian strain is highly similar to a Chinese isolate, suggesting a hidden circulation of this hvKp ST65 K2 lineage.